Confrontation avec le contexte disciplinaire institutionnalisé : réflexion critique des approches écosystémiques de la santé sur la base des expériences des jeunes chercheurs au Canada, en Afrique occidentale et centrale et en Amérique centrale - Mathieu Feagan; Brama Koné; Nicolas Brou; Yveline A. Houenou; Edouard Kouassi; Jerry Spiegel (VertigO)
The experiences of students, young researchers and professionals trained in ecosystem approaches to health (ecohealth) offer new perspectives on the challenge of changing the world in which we live. Guided by the pillars of transdisciplinarity, participation and social/gender equity, ecohealth aims to effectively intervene in complex problems linking environment and health. However, putting these pillars into practice in the field raises challenges that cannot be adequately understood outside of the institutional context that frames the relationship between researchers and the community. What may seem like minor details – for example, arriving in the field, making contact with the community, presenting the research project, collecting data, etc. – remain intimately connected to the mode of knowledge production dominated by the disciplinary structure and current political-economic conditions through which the encounter between researchers and the community occurs. Based on 28 interviews with graduate students and young professionals trained in ecohealth in West and Central Africa, Central America and Canada, and based on observations of ecohealth projects on the ground, this article aims to trace the challenges of mounting an ecohealth project while taking into account the dominant institutional context. After a brief overview of the theory and history of ecohealth, we present some of the main challenges that emerged from efforts to put ecohealth into practice. After situating these challenges into their wider institutional context, we point out key implications and propose certain new policy directions that should prove relevant to other groups working at the interface of environment and health.